The relative age effect on the selection of young athletes and the performance of Brazilian futsal teams - Leonardi, Thiago José; Kunrath, Caito André; Silva, Isabela Freitas da; Rucco, Gabriel da Silva; Aires, Hannah; Berger, Artur Goulart; Cardoso, Marcelo Francisco da Silva (Cuadernos de Psicología del Deporte, 2022)
Aim: The aim of the present study is to assess the effect of relative age on the selection of young athletes and the performance of futsal teams. Methods: The date of birth of 2,676 young athletes (female: n=292; male=2,384) playing in the U-9 to U-20 categories of Brazilian futsal was collected. The athletes were categorized based on quartile and on the semester of birth. The final position of the teams in the tournament was categorized as finalist, semifinalist and non-semifinalist. The chi-square test, the Cramer’s V and multinomial logistic regression models were applied. Results: The data supported the hypothesis about the trend to select athletes who were born in the first months of the year in male teams, but it was not observed in female teams. Additionally, only athletes in the U-13 category who were born in the first semester of the year present 50% chance to be among the finalists in the tournament when they are compared to their peers. Practical application: The relative age had effect on the team of young male athletes, but such an effect was not associated with the positive performance of futsal teams, except for the U-13 category. Thus, coaches of young athletes are recommended to value other factors at the time to select and compose their teams within the herein assessed context.